1985
DOI: 10.1038/bjc.1985.113
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour activity of peroxidases

Abstract: Some time ago Schultz and his colleagues (Schultz et al., 1972; demonstrated that myeloperoxidase, when injected daily into tumour-bearing mice in conjunction with thio-TEPA, causes a significant decrease in the rate of tumour growth. Neither myeloperoxidase nor thio-TEPA alone appeared to be effective, and retardation in tumour growth was only observed as long as treatment was continued.In vitro, myeloperoxidase in the presence of hydrogen peroxide and a halide ion exerts a potent cytotoxic activity against a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 21 publications
0
45
0
Order By: Relevance
“…The heme peroxidase enzymes catalyze H 2 O 2 -dependent oxidation of a range of substrates through a mechanism that, in all cases, involves formation of an oxidized ferryl intermediate (known as Compound I; see Equation 1) that is subsequently reduced by substrate (Equations 2 and 3) (1,2). In the majority of cases, reduction of Compound I occurs by two successive single-electron transfer steps, as follows (where P ϭ peroxidase, HS ϭ substrate, S ⅐ ϭ 1-electron oxidized form of substrate).…”
mentioning
confidence: 99%
“…The heme peroxidase enzymes catalyze H 2 O 2 -dependent oxidation of a range of substrates through a mechanism that, in all cases, involves formation of an oxidized ferryl intermediate (known as Compound I; see Equation 1) that is subsequently reduced by substrate (Equations 2 and 3) (1,2). In the majority of cases, reduction of Compound I occurs by two successive single-electron transfer steps, as follows (where P ϭ peroxidase, HS ϭ substrate, S ⅐ ϭ 1-electron oxidized form of substrate).…”
mentioning
confidence: 99%
“…4 Heme-containing peroxidases are ubiquitous in living organisms and are one of the most extensively studied classes of enzyme (1). Peroxidases catalyze the oxidation of a variety of substrates at the expense of hydroperoxides, most often H 2 O 2 .…”
mentioning
confidence: 99%
“…It has been found that most of the peroxidases: plant peroxidases, cytochrome c peroxidase, chloroperoxidase, lactoperoxidase, etc. are hemeproteins with a common catalytic cycle (Everse et al, 1991). Horseradish peroxidase (HrP) has been most thoroughly studied and frequently used to exemplify the peroxidase reaction cycle:…”
Section: Horseradish Peroxidasementioning
confidence: 99%